The Use of Anglicisms in Spanish Television Commercials of Cosmetics, Hygiene and Personal Care Products - Rodríguez-Medina, María Jesús (HERMES - Journal of Language and Communication in Business, 2016)
This paper analyses the use of English in Spanish television commercials, since no scientific studies have been carried out so far in this field. Although there are a few similar studies of print media, our review of the literature has shown some gaps in the research on Anglicisms used in advertising. English seems to be widely present in television commercials in Spain for different reasons. Marketing and cost-saving strategies of multinational companies together with the prestige of the English language and Anglo-American culture in Spain are some of the primary causes. In our study, we have focused on a corpus of pure Anglicisms (English words which have not been adapted to Spanish) and pseudo-Anglicisms (terms that do not exist in English, though they are similar to English words), found in commercials related to cosmetics, hygiene and personal care products, as part of the research project “Globalisation and Impact of the Anglo-American Culture on Spain”. Five hundred and thirty one commercials of the three main private national television channels in Spain (Tele5, Antena3, LaSexta) and children’s Disney Channel (Spain) were compiled in 2013. The results confirm a considerable presence of pure Anglicisms, English-Spanish code switching, pseudo-Anglicisms and Anglo-American imagery and music in the advertising of products related to cosmetics, hygiene and personal care on Spanish television. Consequently, the link of these products to the prestige of the English-speaking world is reinforced.